Improving the management of inventory in the Rolls-Royce Energy Aftermarket Business - Palmer, John (2011)
The market place in which Rolls-Royce Energy currently operates in is highly competitive. This means that the management of inventory is becoming ever more important, especially when the life cycle of Energy gas turbine engines can be as long as thirty years which are supported by Rolls-Royce’s aftermarket business.